Ethnicity of the “Ethnical Economics” and Social Networks of Migrants - Бредникова, Ольга; Паченков, Олег (Journal of Economic Sociology, 2010)
The paper analyzes the existed concepts of ethnical economics on the basis of the study of the formation principles of social networks by economic migrants. The authors suggest their own ideas about the ethnicity. The object is the economic migrants from the Caucuses and Middle Asia, sailing on the markets in Saint-Petersburg.